Spectral distribution of scattered light from a chemical relaxation system - Marques Júnior, Wilson (2011)
The aim of this work is to describe the light scattering spectra of a quaternary reacting gas mixture from the macroscopic field equations derived from the kinetic BGK-type model proposed by the authors in a previous paper. The study is developed in a hydrodynamic regime for which the system of the field equations of constituent number densities, momentum and temperature of the mixture is closed by the constitutive equations for rate of reaction, diffusion velocities, pressure tensor and heat flux vector. The spontaneous Rayleigh-Brillouin scattering is calculated from the constituent density perturbations of the linearized field equations, and its line shape is drawn for two different mixtures of the Hydrogen-Chlorine system showing the induced chemical reaction effect.